Adaptation to a ketogenic diet modulates adaptive and mucosal immune markers in trained male endurance athletes. (5th October 2020) - Shaw, David M.; Merien, Fabrice; Braakhuis, Andrea; Keaney, Lauren; Dulson, Deborah K.
Abstract : This study examined the effect of short‐term adaptation to a ketogenic diet (KD) on resting and post‐exercise immune markers. Using a randomized, repeated‐measures, crossover design, eight trained, male, endurance athletes ingested a 31‐day low carbohydrate (CHO), KD (energy intake: 4% CHO; 78% fat) or their habitual diet (HD) (energy intake: 43% CHO; 38% fat). On days 0 and 31, participants ran to exhaustion at 70% VO2max . A high‐CHO (2 g·kg −1 ) meal was ingested prior to the pre‐HD, post‐HD, and pre‐KD trials, with CHO (~55 g·h −1 ) ingested during exercise, whereas a low‐CHO (<10 g) meal was ingested prior to the post‐KD trial, with fat ingested during exercise. Blood and saliva samples were collected at pre‐exercise, exhaustion, and 1 hour post‐exhaustion. T‐cell‐related cytokine gene expression within peripheral blood mononuclear cells (PBMCs) and whole‐blood inflammatory cytokine production were determined using 24‐hour multi‐antigen‐stimulated whole‐blood cultures. Multi‐antigen‐stimulated PBMC IFN‐γ mRNA expression and the IFN‐γ/IL‐4 mRNA expression ratio were higher at exhaustion in the post‐KD compared with pre‐KD trial ( P  = 0.003 and P  = 0.004); however, IL‐4 and IL‐10 mRNA expression were unaltered ( P  > 0.05). Multi‐antigen‐stimulated whole‐blood IL‐10 production was higher in the post‐KD compared with pre‐KD trial ( P  = 0.028), whereas IL‐1β, IL‐2, IL‐8, and IFN‐γ production was lower in the post‐HD compared with pre‐HD trial ( P  < 0.01). Salivary immunoglobulin A (SIgA) secretion rate was higher in the post‐KD compared with pre‐KD trial ( P  < 0.001). In conclusion, short‐term adaptation to a KD in endurance athletes may alter the pro‐ and anti‐inflammatory immune cell cytokine response to a multi‐antigen in vitro and SIgA secretion rate.